2022
DOI: 10.1088/0256-307x/39/2/027401
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity with a Violation of Pauli Limit and Evidences for Multigap in η-Carbide Type Ti4Ir2O

Abstract: We report the synthesis, crystal structure, and superconductivity of Ti4Ir2O. The title compound crystallizes in an η-carbide type structure of the space group F d 3 ¯ m … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…( 16 ) does not consider the SOC. The importance of SOC was pointed out by Ruan et al 32 and Shi et al 33 in Ti 4 Ir 2 O, exhibiting the violation of the Pauli limit. Similarly, we can expect that the enhanced μ 0 H c2 (0) of Zr 4 Pd 2 O would be raised from strong SOC.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…( 16 ) does not consider the SOC. The importance of SOC was pointed out by Ruan et al 32 and Shi et al 33 in Ti 4 Ir 2 O, exhibiting the violation of the Pauli limit. Similarly, we can expect that the enhanced μ 0 H c2 (0) of Zr 4 Pd 2 O would be raised from strong SOC.…”
Section: Discussionmentioning
confidence: 90%
“…From the expression, we can understand the strength of SOC proportions to Z 4 within the same electronic orbital. In the case of the Ti 4 Ir 2 O superconductor, we can expect the Ir-5 d orbital hosting enhanced SOC should play an important role for the large μ 0 H c2 (0), and it was found that Ti-3 d and Ir-5 d orbitals hybridize near its Fermi level and the violation of the Pauli limit is a result of a combination of strong-coupled superconductivity, SOC, and strong electron correlation 32 . Furthermore, the large SOC splitting a band structure along Γ-K lines due to the Ir-5 d electrons was weakened by applying pressures, and large μ 0 H c2 (0) undergoes a crossover at 35.6 GPa from well beyond to less than the μ 0 H P 33 .…”
Section: Introductionmentioning
confidence: 99%
“…While we have emphasized nodal planes on which anomalous pseudospin exists, there are also materials for which anomalous pseudospin develops on nodal lines and not on nodal planes. Some such materials also exhibit unusual response to magnetic fields [78][79][80], suggesting a broader range of applicability for anomalous pseudospin superconductivity.…”
Section: Discussionmentioning
confidence: 99%